Perceived Value and e-WOM as Drivers of Customer Engagement: The Mediating Role of Purchase Intention among Generation Z Genshin Impact Users - Dian Irma Aprianti; Dahlia Natalia; Pudjiati Pudjiati; Dimas Ardi Pratama (Khazanah Sosial, 2025)
This study aims to analyze the influence of perceived value and electronic word of mouth (e-WOM) on customer engagement, with purchase intention as a mediating variable, among Generation Z users of the Genshin Impact game application. The background of this research is rooted in the increasing competition within the mobile gaming industry and the growing need for companies to maintain user engagement through experiential value and digital recommendations. This study employed a quantitative approach involving four key variables: perceived value, e-WOM, purchase intention, and customer engagement. Data were collected through an online questionnaire administered to respondents aged 17–28 who had played Genshin Impact, with a minimum sample size of 170 participants. The analysis utilized Structural Equation Modeling (SEM) through WarpPLS 7.0. The results indicate that both perceived value and e-WOM significantly affect customer engagement. Purchase intention was also found to significantly influence engagement. Indirectly, perceived value demonstrated a significant effect on engagement through purchase intention, whereas e-WOM did not exhibit a significant mediating effect. Theoretically, this study strengthens the understanding of user engagement formation within experience-based digital gaming ecosystems. Practically, it provides implications for game developers in designing marketing strategies that prioritize enhanced experiential value and the optimization of e-WOM. The originality of this study lies in its focus on Generation Z users in Indonesia and its integration of four digital engagement variables into a single comprehensive model.